Evaluation of Ribonucleic Acid (RNA) amplification efficiency to determine optimal RNA concentration ranges from formalin-fixed paraffin-embedded rodent tissues for gene expression analysis. (26th March 2015) - Euler, Catherine; Isaacs, Michael; Simic, Damir; Vleet, Terry Van; Gillham, Susan; Michael Peden, W.
Abstract : The goal of this study was to establish Ribonucleic Acid (RNA) amplification efficiencies and determine optimal concentration ranges for downstream real-time reverse transcription-quantitative polymerase chain reaction (RT-qPCR) analyses with RNA isolated from formalin-fixed paraffin-embedded (FFPE) and frozen rat tissues. Messenger RNA was isolated using magnetic particle processing technology. RNA concentrations and integrity were assessed from frozen and FFPE rat liver, lung, kidney, heart, mammary gland, pancreas, skin, and duodenum, and cycle thresholds ( C t s) were obtained from each dilution of an RNA template. PCR amplification efficiencies and optimal template ranges were calculated for FFPE and frozen tissue samples. Calculated percent efficiency evaluations for FFPE and frozen tissues showed that FFPE samples, at the RNA concentrations tested, were of acceptable quality for downstream gene expression analyses.